Clinical practice and outcome of radiotherapy for advanced esophageal squamous cell carcinoma between 2002 and 2018 in China: the multi-center 3JECROG Survey. (4th May 2021) - Li, Chen; Wang, Xin; Wang, Lan; Chen, Junqiang; Zhang, Wencheng; Pang, Qingsong; Zhao, Yidian; Sun, Xinchen; Zhang, Kaixian; Li, Gaofeng; Li, Ling; Qiao, Xueying; et al.
Abstract: Purpose: To determine the survival and prognostic factors of esophageal squamous cell carcinoma (ESCC) patients undergoing radical (chemo)radiotherapy in the era of three-dimensional conformal radiotherapy (3DCRT) and intensity modulated radiotherapy (IMRT) in China. Material and methods: The Jing-Jin-Ji Esophageal and Esophagogastric Cancer Radiotherapy Oncology Group (3JECROG) conducted the first nationwide survey of nine institutions. Detailed information was accumulated on 5185 patients with ESCC who received definitive 3DCRT/IMRT between 2002 and 2018. Relevant prognostic factors were evaluated to assess their influence on overall and progression-free survivals. Results: After a median follow-up time of 47.0 (0.9–157.4) months, the 1-year, 2-year, 3-year and 5-year overall survival rates of the whole group were 69.8%, 46.6%, 37.9% and 30.1%. The 1-year, 2-year, 3-year, and 5-year progression-free survival rates were 54.1%, 36.6%, 30.5% and 24.9%. Multivariate analysis demonstrated that sex, clinical stage, treatment modality and radiation dose were prognostic factors for OS. The survival of patients who received concurrent chemoradiotherapy (CCRT) was better than that of patients who received radiotherapy alone or sequential chemoradiotherapy. Patients receiving adjuvant chemotherapy after CCRT had a better OS than patients receiving CCRT alone. Patients receiving higher radiation dose had a better OS than those patients receiving low-dose radiotherapy. Conclusions: The survival of ESCC patients undergoing radical (chemo)radiotherapy was relatively satisfactory in the era of 3DCRTand IMRT. As the largest-scale multicenter research on esophageal cancer radiotherapy conducted in China, this study establishes national benchmarks and helps to provide references for subsequent related researches.